PENERAPAN STRATEGI PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATERI KESETIMBANGAN KELARUTAN DI KELAS XI IPA SMA NEGERI 1 BANGKINANG KOTA - Sari, Intan Tirta; Azmi, Johni; Holiwarni, Betty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research about the process of oriented guided inquiry learning strategy has been conducted in SMAN 1 Bangkinang Kota. The purpose of this research is to improve the student achievement on the topic equilibrium solubility in class X1 SMAN 1 Bangkinang Kota. The type of this research is experimental research with experiment design randomized control group pretest-posttest. Sample of the research consisted of two classes, a class XI IPA 1 as an experimental class (implemented the process of oriented guided inquiry learning strategy) and class XI IPA 2 as the control class (without the process of oriented guided inquiry learning strategy). T-test was used as analysis technique. Based on the data analysis obtained t > t table i.e 2,40 > 1.67, meaning that the application of the process of oriented guided inquiry learning strategy can improve the student achievement on the subject equilibrium solubility in class X1 SMAN 1 Bangkinang Kota. The influence of POGIL strategy to improvement of the student achievement (Logistic Regression test) as high as 10,9%.Keywords: Student Achievement, The Process Of Oriented Guided Inquiry Learning Strategy,Equilibrium Solubility.